Training on the Use of COD Payment Methods and Their Impact on Buyer Decisions on Shopee E-Commerce - Arsyadona, Arsyadona; Trianda, Rendi Rizky; Syafitri, Nabila (Universitas Islam Negeri Sumatera Utara, 2023)
The purpose of this study is to find out whether there is an influence of COD payments on buyers' decisions, behind the many problems that are detrimental to both sellers and buyers who use this payment option. The research was carried out with a situational approach using the regression method. The sample taken in this study was 40 consumers and was analyzed using a frequency table and an F value test with SPSS Software. The results showed that respondents preferred the COD payment method over other payment methods